Investigation of Sub-Surface Geological and Man-Made Features in and Around Lazimpat - Maharajgunj Area, Kathmandu Valley Using Ground Penetrating Radar (GPR) - A.D.A Chhetri; U.C Bhusal; L.P Paudel (International Association of Lowland Technology, 2020)
Geophysical methods have been used as nondestructive,reliable and economic methods for subsurface detection. Thedepth of investigation ranges from shallow depth of centimeter tohundreds of meters from the surface. Among severalgeophysical methods like Seismic, Electrical, Gravity, Magnetic,Electromagnetic, Radar; Ground Penetrating Radar (GPR) hasbeen used in present research to understand subsurfaceinformation about lithological characteristics and undergroundutilities (pipes, cables) passing along and across the roadalignment between Lazimpat-Maharajgunj road section ofKathmandu. GPR utilizes electromagnetic waves for subsurfacedetection and can effectively facilitate planning, design andexcavation of work. Data acquisition was carried out using SIR20instrument manufactured by Geophysical Survey System, Inc.with central frequency of 270 MHz at seven different locationswhich are further processed with processing software PRISM-2.GPR survey results shows presence of clay, silt, fine to mediumgrained sand with no distinct geological structure, utilities laidalong and across the road alignment at different locations andare marked on respective sections. GPR method can be used fordetecting subsurface geological and man-made features inKathmandu and areas having similar geology; prior toexcavations for infrastructure enhancement project so as tospeed up the work along with reduction/avoidance of damages